Exercise and depression symptoms in chronic kidney disease patients: an updated systematic review and meta-analysis - Xueyi Zhou; Yan Bai; Fan Zhang; Min Gu (Renal Failure)
Objectives To investigate whether exercise intervention is associated with reducing depressive symptoms in chronic kidney disease (CKD) patients.Methods Medline (PubMed), Web of Science, Embase, and the Cochrane Central Register of Controlled Trials (CENTRAL) from inception to February 28, 2024. Randomized controlled trials comparing exercise intervention with usual care or stretching sessions for depression symptoms. Independent data extraction was conducted, and the quality of studies was assessed. A meta-analysis was carried out by using random effects models to calculate standardized mean difference (SMD) with a 95% confidence interval (95% CI) between groups.Results 23 trials with 1561 CKD patients were identified. Exercise interventions are associated with a significant reduction in depression symptoms among CKD patients, with a moderate average SMD of −0.726 (95% CI: −1.056, −0.396; t=-4.57; p < 0.001). Significant heterogeneity was observed (tau2 = 0.408 [95%CI: 0.227, 1.179], I2 = 79.9% [95% CI: 70.5%, 86.3%]). The funnel plot shows potential publication bias. Subgroup analyses showed that the beneficial effects of exercise on depression remained constant across all subgroups. The evidence is deemed as ‘very low’ certainty.Conclusions Our systematic review and meta-analysis showed that exercise intervention was associated with significantly alleviating depression symptoms (certainty of evidence: very low). While the very low certainty of the evidence highlights a need for further research.PROSPERO registration number CRD42021248450.